Techno-anxiety and techno-satisfaction during the COVID-19 pandemic: the case of special education teachers - Al Mulhim, Ensaf Nasser; Almulhem, Fatema Abdullah (Frontiers in Education, 2024)
The objective of this study was to assess the levels of techno-anxiety and techno-satisfaction that special education teachers in Saudi Arabia experienced during the COVID-19 pandemic. We used a survey to gather data from 286 teachers of students with special needs across from early intervention to secondary school (5 -18 years) the Kingdom, and we interviewed 23 teachers (3 early intervention, 13 primary, 2 intermediate, 5 secondary). Quantitative analysis was employed to analyze the survey responses, while qualitative thematic analysis was used for the interview data.The findings showed that the teachers experienced moderate levels of anxiety (a mean of 2.33 out of 4). On the other hand, the teachers expressed satisfaction (a mean of 2.98 of 4) with the distance learning system they used. The study highlights the benefits and challenges associated with implementing distance learning for students with special needs. These findings could help inform the design of distance learning environments and identify the factors that influence teachers' feelings of anxiety or satisfaction during the implementation of distance learning. Additionally, the study's results could encourage parents of students with special needs to foster improved collaboration and cooperation with teachers.